1984
DOI: 10.1007/bf00442584
|View full text |Cite
|
Sign up to set email alerts
|

Blood selenium content and glutathione peroxidase activity in children with cystic fibrosis, coeliac disease, asthma, and epilepsy

Abstract: Long-term selenium status in children from the North-East of Scotland was estimated using whole blood selenium content (BSe) and glutathione peroxidase activity (BGSH-Px). BSe was significantly lower than the reference range in children with cystic fibrosis, coeliac disease and in older patients with phenylketonuria. Whereas BGSH-Px of all the children with coeliac disease and those with cystic fibrosis aged over 6 years matched the reference range, it was reduced in younger patients with cystic fibrosis and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 20 publications
0
17
1
Order By: Relevance
“…This may become more pronounced when having malabsorptions or diseases like cystic fibrosis (CF) which is caused by an autosomal-recessive gene defect. These persons are suffering from altering of their mucose production, predominantly viscose mucose production, resulting in breath insufficience and gastro-intestinal disorders like maldigestion [7][8][9][10][11]. The exact alteration of this mechanism, as well as absence or presence of Se metabolites, is unknown up to now [12].…”
Section: Selenium and Cystic Fibrosismentioning
confidence: 99%
See 1 more Smart Citation
“…This may become more pronounced when having malabsorptions or diseases like cystic fibrosis (CF) which is caused by an autosomal-recessive gene defect. These persons are suffering from altering of their mucose production, predominantly viscose mucose production, resulting in breath insufficience and gastro-intestinal disorders like maldigestion [7][8][9][10][11]. The exact alteration of this mechanism, as well as absence or presence of Se metabolites, is unknown up to now [12].…”
Section: Selenium and Cystic Fibrosismentioning
confidence: 99%
“…Generally, cystic fibrosis leads to a lack of anti-oxidant agents, mostly Se species and Vitamin E in addition to a parallel increase of free radicals, partly caused by broncho-pulmonal infections [13]. A couple of studies proved the reduced Se status of CF patients [7][8][9][10][11]. The analysis of Se species in serum of such patients thus is of great importance.…”
Section: Selenium and Cystic Fibrosismentioning
confidence: 99%
“…However, there was no difference between platelet Se concentration and GPX activity in the patients and the controls. Ward et al 21 showed that blood Se concentrations in treated asthmatic children from the northeast of Scotland were not significantly different from those of a control group, although whole blood GPX was significantly increased. Qujeq et al 22 assessed serum GPX activity and Se concentration in 46 asthmatic patients and 75 age-and sex-matched non-asthmatic subjects and found that the asthmatic patients had significantly lower serum concentrations of Se and GPX than those in controls.…”
Section: Discussionmentioning
confidence: 97%
“…Most authors agree on a decreased Se level and GPX activity in a fraction of the CF population (Dworkin, et al, 1987). Others state that Se deficiency is only significant in CF children below the age of 6 (Ward, et al, 1984). Se deficiencies were also reported in hair of children and teenagers (Savrasova, et al, 2009).…”
Section: Trace Elementsmentioning
confidence: 98%
“…In plasma and RBC (Neve, et al, 1983a) 20 7-19 In plasma and RBC (Neve, et al, 1983b) 14 2-19 In plasma (Richard, et al, 1990) 13 6-15 In plasma (van Caillie-Bertrand, et al, 1982) 20 19-34 In serum (Stead, et al, 1985) 31 3-35 In serum (Michalke, 2004) 15 0-14 − (Ward, et al, 1984) No difference 27 7-20 In plasma (Portal, et al, 1993) Decreased GPX levels 14 2-19 In plasma and RBC (Richard, et al, 1990) 6 − Very low levels in untreated children (Foucaud, et al, 1988) 20 − Mild deficiency in children with pancreatic enzyme replacement (Foucaud, et al, 1988) 15 0-14 Significant decrease in children below the age of 6 (Ward, et al, 1984) No difference 13 10-22 − (Percival, et al, 1995) Se levels in other analytes − 1-18 Decreased Se levels in hair of CF patient from Stavropol region, Russia (Dworkin, et al, 1987) Zinc (Zn)…”
Section: -19mentioning
confidence: 99%